Proceedings of Annual Geological Conference 2000, Shangri-La Hotel, Penang, 8-9 September 2000 - Annual Geological Conference 2000 (2000 : Penang); Teh, Guan Hoe, 1946-; Pereira, Joy Jacqueline, 1965-; Ng, Tham Fatt, 1964-; Persatuan Geologi Malaysia (Geological Society of Malaysia) (Kuala Lumpur : Geological Society of Malaysia, 2000)
47